2023
DOI: 10.3390/ijms24021229
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue-Derived Extracellular Vesicles Contribute to Phenotypic Plasticity of Prostate Cancer Cells

Abstract: Metastatic prostate cancer is one of the leading causes of male cancer deaths in the western world. Obesity significantly increases the risk of metastatic disease and is associated with a higher mortality rate. Systemic chronic inflammation can result from a variety of conditions, including obesity, where adipose tissue inflammation is a major contributor. Adipose tissue endothelial cells (EC) exposed to inflammation become dysfunctional and produce a secretome, including extracellular vesicles (EV), that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…The most recent study by Mathiesen et al, determine the contribution of omental (OM) and subcutaneous (SC) adipose tissue EVs (ATEVs) in metastatic prostate cancer (PC3ML cells) and evaluated the miRNA cargo with NanoString array. Forty-eight miRNAs were detected in SC ATEVs, 55 in OM ATEVs and 44 in both; transcriptomic analyses on PC3ML after treatment with ATEVs showed differentially expressed genes associated with proliferation, invasion and glycolysis and were validated with functional assays [98].…”
Section: Adipocytes As An Important Source Of Evs In the Tmementioning
confidence: 86%
“…The most recent study by Mathiesen et al, determine the contribution of omental (OM) and subcutaneous (SC) adipose tissue EVs (ATEVs) in metastatic prostate cancer (PC3ML cells) and evaluated the miRNA cargo with NanoString array. Forty-eight miRNAs were detected in SC ATEVs, 55 in OM ATEVs and 44 in both; transcriptomic analyses on PC3ML after treatment with ATEVs showed differentially expressed genes associated with proliferation, invasion and glycolysis and were validated with functional assays [98].…”
Section: Adipocytes As An Important Source Of Evs In the Tmementioning
confidence: 86%
“…Interestingly, besides the TEV-mediated signaling, several recent studies have identified the role of stromal cell-derived EVs in supporting cancer progression by affecting the tumor cells, thus indicating a bidirectional EV-mediated crosstalk in cancer. EVs derived from adipocytes and adipose-endothelial cells were found to induce proliferation, migration and invasion of the recipient prostate cancer cells, thereby promoting metastasis in prostate cancer ( 64 , 65 ). While CAFs were found to support the surrounding tumor cells by transferring tumor-supportive signals via EVs, thereby contributing to tumor growth and metastasis in several cancer types ( 62 , 66 68 ).…”
Section: Tumor Derived Evsmentioning
confidence: 99%
“…Mathiesen found that PC3ML metastatic prostate cancer cells proliferated significantly after contacting with EVs from adipose tissue. This may be attributed to the transcription factor twist family bHLH transcription factor 1 (twist1), which is critical for secondary tumor growth (Mathiesen et al 2023 ).…”
Section: Research Progress Of Ti-evs In Tumorsmentioning
confidence: 99%
“…Adipose Ti-EVs derived from overweight and obese people increased melanoma migration compared with those from the lean individuals (Lazar et al 2015 ). miRNAs contained in adipose Ti-EVs, such as miR-128 and miR-155, were also found to promote cancer invasion and metastasis, especially in a pro-inflammatory environment (Mathiesen et al 2023 ). Moraes found that ADSC-derived EVs may activate the Janus kinase (JAK)/signal transducer and activator of transcription (STAT-3) pathway through epidermal growth factor receptor 1 (EGFR-1)/IL-6, thereby promoting breast cancer cell migration and metastasis (Moraes et al 2021 ).…”
Section: Research Progress Of Ti-evs In Tumorsmentioning
confidence: 99%
See 1 more Smart Citation